Revealing the distinctiveness character of Pulau Suri floating market / Faridatul Akma Ab Latif ... [et al.] - Ab Latif, Faridatul Akma; Mohamed Ali, Salina; Mat Isa, Masbiha; Mohd Zain, Ili Najwa Syamimi (Universiti Teknologi MARA, Perak, 2023)
The Pulau Suri floating market is the first-ever Malaysian floating market. The market offers a distinct character which attracts domestic and international visitors. However, in the midst of rapid global growth, floating markets have to compete with those in other countries to attract more visitors. This requires such markets to develop distinctiveness and character. This research aims to reveal the existing physical and sociocultural characters embedded in the floating market at Pulau Suri, Tumpat. The objective is to examine how both parameter elements contribute to the establishment of Pulau Suri's floating market distinctiveness character. Qualitative descriptive methods were employed, including semi-interviews, observations and a field-survey. The data collection method for the field-survey was guided through the use of groupings of elements analysis, including historic and site-physical background; land use and activities; and accessibility and social-cultural factors. This study reveals ten elements affecting the distinctiveness character of Pulau Suri's floating market. These elements are significant elements for understanding, safeguarding, catalyst in the development of floating markets which is under of creative rural tourism.